2016
DOI: 10.1007/s00429-016-1231-z
|View full text |Cite
|
Sign up to set email alerts
|

Directional asymmetry in the volume of the human habenula

Abstract: Brain asymmetry is a conserved feature in vertebrates. The dorsal diencephalic habenular complex shows conspicuous structural and functional asymmetries in a wide range of species, yet it is unclear if this condition is also present in humans. Addressing this possibility becomes relevant in light of recent findings presenting the habenula as a novel target for therapeutic intervention of affective disorders through deep brain stimulation. Here we performed volumetric analyses in postmortem diencephalic samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 24 publications
5
45
1
Order By: Relevance
“…In our study, we observed no significant differences between right and left habenula functional connectivity (see supplemental figures S4 and S5 for separate connectivity maps of left and right habenula). However, a significant volumetric difference was found, with the left habenula larger than the right, which replicates previous volumetric findings in humans (Ahumada-Galleguillos et al, 2016). One notes that this anatomical difference does not necessarily imply functional lateralization.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we observed no significant differences between right and left habenula functional connectivity (see supplemental figures S4 and S5 for separate connectivity maps of left and right habenula). However, a significant volumetric difference was found, with the left habenula larger than the right, which replicates previous volumetric findings in humans (Ahumada-Galleguillos et al, 2016). One notes that this anatomical difference does not necessarily imply functional lateralization.…”
Section: Resultssupporting
confidence: 90%
“…Following manual tracing of the habenula, the volumes of the left and right habenulae for each subject were computed separately. Because of reports of structural and functional laterality differences (Ahumada-Galleguillos et al, 2016; Bianco and Wilson, 2009; Hétu et al, 2016), left and right habenula volumes were compared using a paired t-test.…”
Section: Methodsmentioning
confidence: 99%
“…In craniates, the dorsal diencephalic epithalamic region is asymmetric in a wide range of species, including fishes (agnathans, chondrichthyans and teleosts), amphibians and amniotes (e.g. lizards, chick and rodents) (reviewed in [14]), and recent reports also extend this asymmetric feature to humans [15,16]. Asymmetries comprise the bilaterally paired habenular nuclei (Hb) and some midline components of the pineal complex, and show significant variations in morphology, and in the extent and sidedness of L-R differences among species [14,[17][18][19].…”
Section: Nodal and Nervous System Asymmetry Across Metazoansmentioning
confidence: 99%
“…Segmentation of the human habenula in in vivo neuroimaging is challenging due to its small size (37.2/34.2 mm 3 (Ahumada‐Galleguillos et al, ) or 30.9/33.2 mm 3 (Ranft et al, ) for left/right habenula, respectively from postmortem histology in deceased subjects without reported cerebral illness or neuropathy) and its low anatomical contrast to the neighboring dorsomedial thalamus. A majority of previous in vivo human habenula volumetric studies have used manual contrast‐based (Carceller‐Sindreu et al, ; Savitz et al, ; Savitz et al, ) or geometric segmentation (Lawson, Drevets, & Roiser, ) on T1‐weighted (T1w) 3T MRI, while more recently, manual contrast‐based segmentation of the habenula from ultra‐high field (7T) T1 maps has also been reported (Schmidt et al, ).…”
Section: Introductionmentioning
confidence: 99%